2009
DOI: 10.4161/cc.8.17.9403
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome cohesion and the spindle checkpoint

Abstract: Accurate chromosome segregation constitutes the basis of inheritance. Mistakes in chromosome segregation during mitosis lead to aneuploidy, a common feature of tumors. The accuracy of chromosome segregation is governed by a complex network of processes which ensure that each daughter cell receives the correct number of chromosomes. Herein we review recent developments in the understanding of chromosome segregation, focusing on the cohesion that holds the sister chromatids together and the spindle checkpoint wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 115 publications
(128 reference statements)
0
13
0
Order By: Relevance
“…The cohesin complex functions to hold chromatin strands within a ring-like structure composed of the four core components (16). Although its canonical and best-established role is to maintain the polarity of sister chromatids during mitosis, cohesin is also involved in double-stranded DNA damage repair and regulation of transcription (17).…”
Section: Phenotypic Consequences Of Cohesin Complex Mutations In Hspcsmentioning
confidence: 99%
“…The cohesin complex functions to hold chromatin strands within a ring-like structure composed of the four core components (16). Although its canonical and best-established role is to maintain the polarity of sister chromatids during mitosis, cohesin is also involved in double-stranded DNA damage repair and regulation of transcription (17).…”
Section: Phenotypic Consequences Of Cohesin Complex Mutations In Hspcsmentioning
confidence: 99%
“…Nonetheless, several genes have been implicated to play a contributory/causal role and include (but are not limited to) genes involved in: (1) centrosomal structure/duplication [ 155-157 ]; (2) DNA repair [ 158-160 ]; (3) mitotic checkpoint maintenance [ 161,162 ]; (4) chromatid cohesion [ 163 ]; (5) chromatin organization [ 164 ]; and (6) the formation/function of the spindle and other components of the mitotic machinery [ 165,166 ] (Figure 5). Perturbations in genes involved in histone methylation or small interfering RNAs have also been noted to lead to disturbances in chromosomal malsegregation or kinetochore protein organization, respectively [ 167,168 ].…”
Section: Acquired Autosomal Aneuploidy In Healthy Individualsmentioning
confidence: 99%
“…Lately, several studies also indicated/confirmed the role of cohesin (other subunits) in spindle poles/centrosomes independently. [46][47][48][49][50] It would be useful if spindle pole assembly. Undoubtedly, more future work will be required to validate and refine this model (Fig.…”
Section: Npc Function In Mitotic Apparatus Orchestration During Mitosismentioning
confidence: 99%